Deformation Wave Hardening of Metallic Materials - A.V. Kirichek; D.L. Solov’ev; A.Yu. Altuhov (Журнал нано- та електронної фізики)
The article deals with the machine parts hardening by means of deformation waves generated by the impact system with a waveguide as an intermediary member. The conditions for the efficient use of impact energy for elastoplastic deformation of the processed material and creation of the deep hardened surface layer.